Toxic effects of Canavalia ensiformis L-(Leguminosae) on laboratory colonies of Atta sexdens L-(Hym., Formicidae) - Hebling, MJA; Bueno, O. C.; Pagnocca, F. C.; da Silva, O. A.; Maroti, P. S. (Blackwell Wissenschafts Verlag Gmbh, 2000)
Laboratory colonies of the leafcutting ants Atta sexdens that were fed daily with leaves of Canavalia ensiformis showed a high ant mortality, and a significant decrease in fungal garden volume, with complete depletion of nests after 11 weeks of treatment.